Sleep and dietary patterns in pregnancy : findings from the GUSTO cohort - Tham, Elaine K. H. (2018)
Evidence on the association between sleep, diet, and eating behaviors in pregnant women is lacking. We examine this in a cohort of apparently healthy pregnant women. At 26–28 weeks gestation, 497 participants completed the Pittsburgh Sleep Quality Index to assess sleep and a 24-h recall to assess dietary intake. Diet quality was assessed by the Healthy Eating Index for pregnant women in Singapore (HEI-SGP) score and previously derived dietary patterns (vegetables-fruit-rice, seafood-noodles, and pasta-cheese-meat pattern). Eating behaviors studied included the longest night-time fasting interval, frequency of consumption occasions, energy from discretionary foods, and nighttime eating. Adjusted means were estimated between poor/good quality and short/normal sleepers using linear regressions, including covariates. Good sleep quality versus poor sleep quality, was associated with better diet quality (mean HEI-SGP 54.6 vs. 52.0; p = 0.032), greater adherence to the vegetables-fruit-rice pattern (mean 0.03 vs. −0.15; p = 0.039), lesser adherence to the seafood-noodle pattern (mean −0.14 vs. 0.03; p = 0.024), and a trending lower calories from discretionary foods (mean 330.5 vs. 382.6 kcal; p = 0.073), after adjusting for covariates. After additional adjustment for anxiety, only sleep quality and the seafood-noodle pattern remained significantly associated (p = 0.018). Short sleep was not associated with any diet or eating behavior. In conclusion, good sleep quality is associated with a better diet quality and a greater adherence to the vegetable-fruit-rice pattern, but with lesser adherence to the seafood-noodle diets in pregnant women.